A Poverty-Focused Evaluation of Commodity Tax Options - Essama-Nssah, B. (World Bank, Washington, DC, 2012)
The difficulties faced by many developing countries in raising revenue from direct taxes have forced them to rely heavily on indirect taxes to finance development interventions. The purpose of this paper is to show how to identify socially desirable options for commodity taxation in the context of a poverty reduction strategy. Within the logic of social evaluation the author assesses tax options on the basis of value judgments underlying members of the additively separable class of poverty measures. The criterion hinges on both the pattern of consumption of each commodity and the price elasticity of the poverty measure used. An application of this methodology to data for Guinea shows that many components of food expenditure (particularly cereals, grains, and roots) would be good candidates for exemption from value-added tax. Even though expenditure on health and education is distributed in favor of the non-poor, their importance for human capital development argues for a program of targeted subsidies in a broader context of cost recovery.